2009
DOI: 10.1007/s11244-009-9358-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Al2O3 and Ag/Al2O3 for Lean Reduction of NO x with Dimethyl Ether

Abstract: Lean reduction of NO x with DME occurs with high selectivity to N 2 over Al 2 O 3 between 300°C and 550°C with a maximum of 47% at 380°C, and with lower selectivity over Ag/Al 2 O 3 between 250°C and 400°C due to the catalysts' sensitivity to gas phase radical reactions and activity for NO x reduction with methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In a previous study, the NO x conversion was shown to increase sharply at the on-set temperature for the gas phase reactions at 300°C during DME-SCR over c-Al 2 O 3 [4]. The interpretation of this observation was that the gas phase reactions promote NO x conversion above 300°C over c-Al 2 O 3 due to the formation of NO 2 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a previous study, the NO x conversion was shown to increase sharply at the on-set temperature for the gas phase reactions at 300°C during DME-SCR over c-Al 2 O 3 [4]. The interpretation of this observation was that the gas phase reactions promote NO x conversion above 300°C over c-Al 2 O 3 due to the formation of NO 2 .…”
Section: Introductionmentioning
confidence: 89%
“…Two of the most promising catalyst materials for hydrocarbon-SCR, i.e. Ag/Al 2 O 3 and Cu-ZSM-5 show only minor activity for NO x reduction with DME [3][4][5], but good activity of up to 68 and 85% has been reported over pure c-alumina, Mo/Al 2 O 3 and Co/Al 2 O 3 [4,6,7]. One of the differences between DME and other reducing agents is the occurrence of gas phase radical reactions in mixtures of DME, NO and O 2 at temperatures around and above 300°C.…”
Section: Introductionmentioning
confidence: 99%
“…Over the In/Al 2 O 3 catalyst the maximum conversion of NO x is 45% whereas no NO x conversion at all can be observed over the Ag/Al 2 O 3 catalyst. It has been reported by Tamm et al [50] that DME undergoes gas phase radical reactions with NO, O 2 and H 2 O, which change the composition of the gas phase considerably before reaching the catalyst. A catalyst suited for DME-SCR should therefore have other properties than conventional HC-SCR catalysts; it should have a high capability to reduce NO x using partially oxidized C 1 -hydrocarbons, not needing to be able to activate the hydrocarbon, and it should not unselectively oxidize species previously formed in the gas phase.…”
Section: Dme As the Reductantmentioning
confidence: 99%
“…Above 200°C, the equilibrium of this reaction favors the formation of methanol with less than stoichiometric amount of water, whereas above 350°C, the major part of the DME has already reacted in the gas phase and is therefore no longer available for hydrolysis over the catalyst [50]. DME gas phase reactions are initiated by the splitting of DME to an H 3 CO˙ and a CH 3˙ radical.…”
Section: Dme As the Reductantmentioning
confidence: 99%
“…Factors which contribute to the catalytic properties of a bimetallic catalyst include: (a) the surface composition of the noble metal and (b) the strength of interaction between the noble metal and the catalyst support [19]. Silver has recently gained much interest for low temperature NO x reduction [20] and CO oxidation [21]. Thus, it could be a suitable catalyst for many redox reactions like VOC oxidation.…”
Section: Introductionmentioning
confidence: 99%